MAKNA ADAT NYAMBAI DAN PERUBAHANNYA - Andika Andika; Bartoven Vivit Nurdin (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2012)
This research intend to assess nyambai tradition and the alterationon marga Liwa Lampung Barat. Lampung society culture have a unique in implementation procedures. However the implementation and nyambai tradition implementation procedures has been changes. This research in influenced by Van Gennep (1960) argument about Rites of passage and Clifford Geertz (1973) argument about meaning and symbolic. Qualitative research methods are used to understand the meaning of nyambai tradition and the changes. Location of this research carried out in the Padang Cahya village Liwa Lampung Barat. Data collection techniques were used is observasi partisipant and depth interviews. The results of this research indicate that nyambai tradition it is a constitute cultural identity, avidence the persistence of Aristocratic form of solidaritty and decency, as well as the changes status of single to marriage life. The changes that happened to the nyambai procesion is ; procedure dress up, dress motif, the tools used in nyambai procession, and nyambai process implementation.